Effect of periodontal treatment on preclinical Alzheimer's disease—Results of a trial emulation approach - Christian Schwahn; Stefan Frenzel; Birte Holtfreter; Sandra Van der Auwera; Christiane Pink; Robin Bülow; Nele Friedrich; Henry Völzke; Reiner Biffar; Thomas Kocher; Hans J. Grabe (2021)
We investigated the relationship between periodontal treatment and pre-clinical Alzheimer's disease (AD).In this quasi-experimental design, 177 periodontally treated patients from the "Greifswald Approach to Individualized Medicine" cohort, which used the same protocols as the population-based Study of Health in Pomerania TREND (SHIP-TREND), and 409 untreated subjects from SHIP-TREND were analyzed. Subjects were younger than 60 years at the magnetic resonance imaging examination, with a median observation period of 7.3 years. Imaging markers for brain atrophy in late-onset AD and brain aging were used as the outcomes.Robust to sensitivity analyses, periodontal treatment had a favorable effect on AD-related brain atrophy (-0.41; 95% confidence interval: -0.70 to -0.12; P = .0051), which corresponds to a shift from the 50th to the 37th percentile of the outcome distribution. For brain aging, the treatment effect was uncertain.Periodontitis is related to pre-clinical AD in our population.